Phytochemical Compounds and Antimicrobial Activity of Extracts of Bamboo Against Staphylococcus aureus and Escherichia coli: Extracts of Bamboo Leaves and Roots - Musyimi, David Mutisya; Khasabulli Buyela, Daniel; Mbilu Kiema, Francis; Chebii, T. K. (Archives of Ecotoxicology, 2023)
Plants contain bioactive compounds which can be used to develop novel antibiotics. There is need to search for new antimicrobial compounds to address the problem of microbial resistance against antibiotics. Little research has been done on phytochemical and antimicrobial activity of Bambusa vulgaris. The study was designed to screen phytochemical compounds present in the roots and leaves extracts and to test antimicrobial activity of the extracts of Bambusa vulgaris against Staphylococcus aureus and Escherichia coli. Plants were collected from Maseno University Botanic Garden. Roots and leaves were dried separately, ground into fine powder and extracted using Soxhlet method. Phytochemicals: flavonoids, saponins, terpenoids, tannins, alkaloids and glycosides were tested. Thin layer chromatography plate was coated with silica gel. n-Hexane and Ethyl acetate were used as solvents in the ratio 2:3 respectively. Plant extracts were prepared; 25%, 50%, 75%, and100% (stock extract) and Positive control (Amoxicillin). The bacteria were inoculated into the nutrient agar. Antimicrobial activity of acetone extracts of leaves and roots were carried out by disc diffusion method. Diameter of inhibition zones was measured using a ruler. The leaves extracts were found to contain saponins, flavonoids, glycosides tannins and terpernoids. The root extracts contained saponins, glycosides and tannins. TLC revealed that there were 7 spots in the leaves and 4 spots in roots extract. Increase in concentration of the leaves and roots extracts of Bambusa vulgaris significantly inhibited the growth of Staphylococcus aureus and Escherichia coli. Leaves extracts showed a higher inhibition activity compared to roots. The growth inhibition may be attributed to the presence of the various phytocompounds. The study has shown that Bambusa vulgaris leaf methanol extract has antimicrobial activity against gram positive (Staphylococcus aureus) and gram negative (Escherichia coli) bacteria and hence can be used as source of bioactive agents to control these pathogens.